Hubungan antara Efikasi Diri dengan Problem-Solving dalam Mengerjakan Skripsi Mahasiswa Psikologi Universitas Islam Raden Rahmat - Vardia, Melly Amalia; Kamilah, Nur Fitrotul (Universitas Negeri Malang, 2022)
Abstract: This study examines the relationship between self-efficacy and problem solving on thesis of psychology students at Universitas Islam Raden Rahmat Malang. The hypothesis for this study is there is a positive relationship between self-efficacy and problem solving in psychology students who were preparing a thesis in Universitas Islam Raden Rahmat Malang. Respondents in this study were 40 psychology students who were preparing a thesis, sample of this study are student class of 2014, 2015, and 2016 which were selected using non-probability sampling techniques. The data was collected using a self-efficacy scale and a problem-solving scale. The self-efficacy scale has a reliability coefficient of 0.884 and the problem solving coefficient scale has a reliability of 0.882. The data analysis technique in this study used the Pearson product moment using SPSS 24 for windows. The results of the data analysis show that there is a positive and significant relationship between self-efficacy and problem solving in the final project of the Raden Rahmat Islamic University Psychology student with a significance value of p = 000 <0.05 with a coefficient of r = 0.678. Abstrak: Penelitian ini mengkaji hubungan antara efikasi diri dengan problem-solving dalam mengerjakan skripsi mahasiswa Psikologi Universitas Islam Raden Rahmat. Hipotesis dalam penelitian ini adalah terdapat hubungan yang positif antara efikasi diri dengan problem-solving. Responden dalam penelitian ini adalah 40 mahasiswa tingkat akhir di prodi Psikologi yang sedang menyusun skripsi terdiri dari angkatan 2014, 2015 dan 2016 yang dipilih dengan menggunakan teknik sampling total. Pengumpulan data dilakukan menggunakan skala efikasi diri dan skala problem-solving. Skala efikasi diri terdiri dari 25 item dengan koefisien reliabilitas sebesar 0,884 dan skala problem-solving terdiri dari 28 item dan memiliki koefisien reliabilitas sebesar 0,882. Teknik analisis data dilakukan dengan uji korelasi product moment menggunakan perangkat lunak pengolah data statistik SPSS 24 for windows. Hasil analisis data menunjukkan bahwa terdapat hubungan yang positif dan signifikan antara efikasi diri dengan problem-solving dalam mengerjakan skripsi mahasiswa psikologi Universitas Islam Raden Rahmat, dengan nilai signifikansi p= 000 <0,05 dengan koefisien r= 0,678.